2023
DOI: 10.1186/s12887-023-03894-6
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study of relationships between social risks and prevalence and severity of pediatric chronic conditions

Abstract: Background To examine the differential relationships between seven social risk factors (individually and cumulatively) with the prevalence and severity of asthma, attention deficit hyperactivity disorder (ADHD), autism spectrum disorder (ASD), and overweight/obesity in children. Methods Using the 2017–2018 National Survey of Children's Health, we examined associations between social risk factors (caregiver education, caregiver underemployment, disc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Most clinical research on social factors and childhood obesity has focused on social risks. In a large, cross-sectional study from the 2017–2018 National Survey of Children's Health, researchers examined associations of seven social risks with four chronic conditions: asthma, attention deficit disorder (ADHD), autism spectrum disorder (ASD), and overweight/obesity (BMI ≥ 85th percentile for age and sex) among children [16 ▪ ]. Among children ages 10–17 years, food insecurity was associated with higher likelihood and greater severity of overweight/obesity [16 ▪ ].…”
Section: Social Factors and Development Of Childhood Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…Most clinical research on social factors and childhood obesity has focused on social risks. In a large, cross-sectional study from the 2017–2018 National Survey of Children's Health, researchers examined associations of seven social risks with four chronic conditions: asthma, attention deficit disorder (ADHD), autism spectrum disorder (ASD), and overweight/obesity (BMI ≥ 85th percentile for age and sex) among children [16 ▪ ]. Among children ages 10–17 years, food insecurity was associated with higher likelihood and greater severity of overweight/obesity [16 ▪ ].…”
Section: Social Factors and Development Of Childhood Obesitymentioning
confidence: 99%
“…In a large, cross-sectional study from the 2017–2018 National Survey of Children's Health, researchers examined associations of seven social risks with four chronic conditions: asthma, attention deficit disorder (ADHD), autism spectrum disorder (ASD), and overweight/obesity (BMI ≥ 85th percentile for age and sex) among children [16 ▪ ]. Among children ages 10–17 years, food insecurity was associated with higher likelihood and greater severity of overweight/obesity [16 ▪ ]. This is one of a few recent studies that has examined associations between multiple social risks and multiple pediatric chronic conditions, but prior research has shown relationships between increasing cumulative social risk and obesity early in childhood [17].…”
Section: Social Factors and Development Of Childhood Obesitymentioning
confidence: 99%
“…In 2022, rates of food insecurity were significantly higher than the previous year, at 12.8% of United States (US) households and 17.3% of households with children [ 1 ]. In children, food insecurity is associated with poor diet quality [ 6 ], poor health [ 7 ], excess healthcare utilization [ 8 , 9 ], and lower cognitive performance [ 10 ]. Also, households experiencing food insecurity have approximately $2400 greater annual healthcare expenditures versus households experiencing food security [ 11 ▪ ].…”
Section: Introductionmentioning
confidence: 99%
“…There is a wealth of literature describing the relationship between selected SDOH factors and childhood obesity using cross-sectional analyses. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] However, these cross-sectional studies assume that all children with obesity are a homogeneous group with similar growth patterns, but the obesity growth pattern of children while developing obesity could have different implications for intervention. 35 For example, children who have obesity from birth may have genetic and epigenetic risk factors and intervention may need to occur in the perinatal period, whereas children born with normal weight but then develop obesity during early childhood may benefit from interventions that can impact their environment and lifestyle.…”
Section: Introductionmentioning
confidence: 99%